2021
DOI: 10.3389/fcimb.2021.694020
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Interactions Between Mosquitoes and Mosquito Viruses

Abstract: Mosquitoes not only transmit human and veterinary pathogens called arboviruses (arthropod-borne viruses) but also harbor mosquito-associated insect-specific viruses (mosquito viruses) that cannot infect vertebrates. In the past, studies investigating mosquito viruses mainly focused on highly pathogenic interactions that were easier to detect than those without visible symptoms. However, the recent advances in viral metagenomics have highlighted the abundance and diversity of viruses which do not generate mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 139 publications
(178 reference statements)
1
32
1
Order By: Relevance
“…Unlike arboviruses, which have dual host tropism (vertebrates and arthropod vectors), ISVs replicate exclusively in insect populations and cannot replicate in vertebrate cells or infect humans [ 41 , 116 , 117 ]. Therefore, being naturally associated with arthropods, they can be considered members of viral communities of insects exclusively (viromes), and are not considered pathogens [ 104 , 117 ]. In adult insects, the highest proportion of ISVs characterized so far correspond to RNA viruses [ 104 ] without causing apparent affectation, suggesting their high adaptation and relationship with insects [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike arboviruses, which have dual host tropism (vertebrates and arthropod vectors), ISVs replicate exclusively in insect populations and cannot replicate in vertebrate cells or infect humans [ 41 , 116 , 117 ]. Therefore, being naturally associated with arthropods, they can be considered members of viral communities of insects exclusively (viromes), and are not considered pathogens [ 104 , 117 ]. In adult insects, the highest proportion of ISVs characterized so far correspond to RNA viruses [ 104 ] without causing apparent affectation, suggesting their high adaptation and relationship with insects [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, being naturally associated with arthropods, they can be considered members of viral communities of insects exclusively (viromes), and are not considered pathogens [ 104 , 117 ]. In adult insects, the highest proportion of ISVs characterized so far correspond to RNA viruses [ 104 ] without causing apparent affectation, suggesting their high adaptation and relationship with insects [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are considered promising for many applications, from vaccine development to arbovirus transmission control tools ( 3 ). Nevertheless, our knowledge of many important aspects of the biology of ISVs is limited, such as their interactions with the vector species that they infect ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cypovirus1 was collected from living and dead stem and cob borer larvae and pupae and examined by electron microscopy showed that particles of Cypovirus1 are shaped icosahedral, which belong to Reoviridae. Cyoovirus1 has a single-shelled capsid [10][11][12][13]. The Cypovirus1 infects the insect larvae of stored grain pests four days after inoculation with the Cypovirus1, causing chronic larvae disease and less-lethal chemical insecticides.…”
Section: Introductionmentioning
confidence: 99%